Optimalization Micro Small And Medium Enterprises Role In Supporting The Halal Tourism Sector In Aceh - Jalilah; Isnaliana; Djakfar, Inayatillah; Amanatillah, Dara (Islamic Business and Management Journal, 2025)
Micro, Small and Medium Enterprises (MSMEs) and the tourism industry have an inseparable link because the availability of halal products or halal services is fundamental in building the halal tourism sector. Therefore, to support the development of the halal tourism sector, optimizing halal products, including MSME products, is one of the keys. This study aims to describe optimizing the role of MSMEs in supporting halal tourism in Aceh. The method used in this research is descriptive analysis with a qualitative approach. The data source used is primary data in the form of interviews with several related agencies, namely LPPOM MPU Aceh, Culture and Tourism Service, Aceh Cooperative and SME Service and MSME actors. The results of this research show that the government, through related institutions, namely LPPOM MPU, the Tourism Office and the Cooperatives and SMEs Service, has made efforts to support the development of the halal MSME sector in order to boost the halal tourism sector through the provision of facilities and various development programs that have been carried out. As for optimizing the role of MSMEs, if we look at the realization of objectives, alternative programs and resources, the role of MSMEs in supporting the halal tourism sector in its implementation is not yet optimal, even though the government itself has attempted various programs and policies to optimize the MSME sector.